Development of reliability analysis toolkit for analysing plant maintenance data - Hussin, H. (EDP Sciences, 2014)
Plant failure and maintenance data can be found in abundance, however, their utilization as a basis for improvement action is not fully optimized. This happens because many reliability analyses based on plant data are tedious and time consuming due to non-standardized nature of the data being recorded. To overcome this issue, this study aims to develop a computer based reliability analysis toolkit to facilitate proper analysis of plant data. The toolkit can be used to perform both exploratory and inferential analysis. The developed toolkit has been demonstrated capable of assisting data gathering and analysis as well producing estimation of reliability measures. Â© 2014 Owned by the authors, published by EDP Sciences.